The Occurrence of Paratuberculosis (Johneâs Disease) in Ruminants in Indonesia Must be Anticipated - ., Tarmudji (Indonesian Animal Sciences Society, 2007)
Paratuberculosis or Johneâs disease is an infectious disease in ruminants (cattle, buffalo, sheep and goat) caused by Mycobacterium avium subspecies paratuberculosis (MAP) and characterized by granulomatous enteritis manifestation. The disease occurs worldwidely and causes great economic losses on domestic livestock industries. Calves are commonly infected soon after birth, with incubation period of either some months or years. Clinical signs observed from 2 to 10 years old of infected cattle are chronic diarrhea and progressive emaciation. Transmission of MAP to calves can occur by nursing the infected dam or got contaminated by fecal material. The pathogens can also be excreted in colostrum or milk, that is why calf can be infected since neonatal period. Infection in progress leads to cause thickening of the intestinal wall, granulomatous and mesenterical lymphnode, Â which Â diffusion Â lesions Â in Â the intestine Â are Â characterized Â by Â the Â macroscopical Â finding.Â In Indonesia, paratuberculosis had been reported in dairy cattle (in West Java) with seroprevalence of 1.67% (3/180). From the serological positive reactors demonstrated MAP of 0.55% (1/180) by fecal cuture examination. Some samples of cattle and buffaloes from North Sumatera were also found positive paratuberculosis antibody against MAP detected by Complement Fixation Test (CFT) at average of 4% (2/50). The presence of positive reactors of paratuberculosis in dairy cattle, beef cattle and buffaloes in Indonesia must be anticipated. These animals are carriers and can shed pathogens, although they do not show clinical signs. It is likely that paratuberculosis can not be detected by conventional diagnostic techniques, therefore, sensitive and early diagnosis techniques must be developed. Â Key words: Paratuberculosis (Johneâs disease), ruminants, clinical signs, Indonesia